HUBUNGAN MOTIVASI DENGAN KINERJA PERAWAT DALAM PENERAPAN SISTIM PEMBERIAN PELAYANAN KEPERAWATAN PROFESIONAL (SP2KP) DI RSUD RADEN MATAHER JAMBI - Yenni Pangabean; Dwi Yunita R; Rahmi Dwi Yanti (Jurnal Akademika Baiturrahim Jambi, 2016)
Backgroumd : Nursing care is the central point. The success of nursing care is determined by the selection of professional nursing care delivery methods (SP2KP). SP2KP is a framework that defines four elements, namely standard, the nursing process, nursing education, and the system of Professional Nursing Services. Method : The study was conducted to determine the relationship of motivation with the performance of nurses in the application of SP2KP. The study was conducted using a quantitative approach, the cross-sectional design and the use of stratified random sampling as a sampling technique. Sample was167nurses in the inpatient unit. Result:The results showed 58.7% as poor motivation and performance of56.3% of nurses in the application of low SP2KP. Results of the bivariate analysis showed no relationship between motivation and performance in the application SP2KP nursein Raden Mattaher hospitals Jambi with p-value of 0.045. Conclusion of this study is that nurses have poor motivation and poor performance in the application SP2KP. For Raden Mattaher hospitals Jambi to improve performance motivation nurses need to be given training related to SP2KP and reward.